CESAS: Networking to advance sustainability through research, education and engagement - Griswold, Wendy; Saulters, Oral; Erickson, Larry E. (Kansas State University, 2009)
The Consortium for Environmental Stewardship and Sustainability (CESAS) is a network of diverse partner organizations choosing to work collaboratively to advance sustainability, expand knowledge base-capacity and explore new frameworks of progress (sustainable development). This Consortium brings together cooperative groups focused on sustainability that integrate and connect multidisciplinary research and education efforts in the areas of science, engineering, economics, and social science. CESAS partners include educational institutions, non-profit groups, industry/business, and government. This poster presentation highlights initiatives, approaches and past CESAS activities, including dialogs and seminars focused on engaging stakeholders in discussion and learning about sustainability and environmental stewardship issues related key topics such as natural resource management, climate change, wind, other renewable energies, and food. The consortium also coordinates a speakers’ bureau, which provides communities and other groups with access to expertise and information related to sustainable practice, initiatives, and issues. Overall, the CESAS model serves to transcend traditional (institutional) boundaries while providing a proactive forum for idea exchange, technical outreach, and creative problem-solving.
Keywords: Sustainable development; Environmental stewardship; Natural resources; Climate change; Renewable energy; Consortium for Environmental Stewardship and Sustainability